Synergetic Effects Leading to Coke‐Resistant NiCo Bimetallic Catalysts for Dry Reforming of Methane. Issue 3 (8th January 2015) - Li, Lidong; Anjum, Dalaver H.; Zhu, Haibo; Saih, Youssef; Laveille, Paco V.; D'Souza, Lawrence; Basset, Jean‐Marie
Abstract A new dry reforming of methane catalyst comprised of NiCo bimetallic nanoparticles and a Mgx(Al)O support that exhibits high coke resistance and long‐term on‐stream stability is reported. The structural characterization by XRD, TEM, temperature‐programmed reduction, and BET analysis demonstrates that the excellent performance of this catalyst is ascribed to the synergy of various parameters, including metal‐nanoparticle size, metal–support interaction, catalyst structure, ensemble size, and alloy effects.